Reporting sample size calculations for randomized controlled trials published in nursing journals: A cross-sectional study. (February 2020) - Tam, Wilson; Lo, Kenneth; Woo, Brigitte
Abstract: Background: Prior sample size calculation is essential to ensure that a randomized controlled trial (RCT) has enough power to detect any statistical differences between two groups while not over-recruiting participants. However, the compliance among RCTs published in nursing field is unknown. Objective: To describe the reporting of sample size methodology and parameters used in RCTs published in nursing journals. Design: A cross-sectional database search of all RCTs published in nursing journals was conducted. Setting: 116 journals in the category of nursing. Participants: Not applicable. Methods: A database search was conducted to identify all RCTs published in nursing journals from January 2016 to December 2016. Two-arm RCTs were reviewed to see if sample size estimation was mentioned in the text and if the parameters were sufficient for the estimation. For RCTs with effect size, sample sizes were recomputed and compared with the reported size. Results: Two hundred and twenty-three RCTs were included in this study, and 143 (64.1%) studies mentioned how they obtained their sample sizes. Among these 143 studies, 132 (92.3%), 133 (93.0%), 33 (23.1%), and 84 (58.7%) specified their levels of significance ( α ), powers, tails of the test, and effect size related information, respectively. Only 22 (15.4%) provided all the necessary parameters to compute their sample sizes. Out of the 84 RCTs with effect size information, 49 (58.3%) had a relative difference of less than 25%. Discussion: Around 36% of the RCTs published in nursing journals did not report how they reached their sample sizes. For those that had reported, only 15% provided all the necessary parameters to re-compute their sizes. It is concluded that the methodology and parameters used for sample size determination are inadequately reported in RCTs published in nursing journals.